Pre-concentration of Some Heavy Metals using cloud point extraction - Abd Al-ameer, Aliaa Shakir; Mohan, Hayder Ghaleb (University of Thi-Qar Journal of Science, 2022)
Heavy metals are usually present in trace amounts in real samples such as natural waters, soil and plants samples but many of them are toxic even at very low concentrations, therefore, cloud point extraction (CPE) used for heavy metal separation. The CPE usage comes back to the works of Watanabe and co-workers who recommended the application of CPE by employing the non-ionic surfactants as an alternative solvent for the extraction of metal ions. In principle, CPE depends on the separation of hydrophobic analyte (i.e. inorganic and/or organic analyte) between two phases generated from micellar of non-ionic surfactant solution when heated to its critical cloud point temperature-CPT. In this review, CPE approach and features elucidated. The mechanism phenomena of CPE explained in addition to the methodology of analytical procedure by this process. Then, the significant applications of this method listed for separation of some heavy metals such as ( Cd, Cu and Co). Finally, this review, mentioned the factors that affected on the CPE approach and results. In general, using this kind of analytical process provides a most reliable and trustworthy results with almost simplicity approach.